Configuration of television regulatory authorities in the Andean countries - Suing Ruiz, A. (2016)
© 2016, University of La Laguna. All rights reserved.Introduction. The objective of this research article is to evaluate the adequacy of television regulators in the Andean region according to the international standards set by UNESCO at times of reforms in communications legislation. The hypotheses that guide this research are that television regulators were created by law, that their autonomy has constitutional support, and that their resolutions promote communication rights. Method. The study is based on a qualitative method that involves the review of regulatory documents and resolutions and the analysis of such variables as: regulator-creation laws, regulatory authority types, financial autonomy, purposes, functions, composition and resolutions. Results and conclusions. The legislation of the regulatory authorities aims to cover from their constituent elements to the impacts of the new forms of communication. Colombias national regulatory authority is the regulator in the Andean region with the largest number of functions in relation to the protection of television viewers. The legislation does not guarantee the participation of associations of television professionals that are free from influences nor that their members of the regulators are qualified to perform their job. The resolutions adopted by the television regulatory authorities have focused on the regulation of the administrative aspects of television.